Sexual Function in Cervical Cancer Patients Based on Female Sexual Function Index Questionnaire at Dr. Hasan Sadikin Central General Hospital From 2018 – 2023 - Zakaria, Bangbang Ahmad Kholila Muhyiddin Abadi; Rinaldi, Andi; Zulvayanti, Zulvayanti (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: To describe the sexual function of cervical cancer patients undergoing radiation therapy at RSHS using the Female Sexual Function Index (FSFI) questionnaire.Methods: This cross-sectional study involved cervical cancer patients who received radiation therapy at RSHS between January 2018 and December 2023. Data were collected using the FSFI questionnaire and were analyzed descriptively.Results: Among 100 patients aged 15 to 70 years, the participants experienced overlapping symptoms. The most frequently reported dysfunctions were vaginal dryness (90.63%), orgasm disorders (79.17%), dyspareunia (64.58%), and decreased libido (58%). Comorbidities included hypertension, diabetes mellitus, and urinary tract infections.Conclusion: Most cervical cancer patients receiving radiation therapy experience sexual dysfunction, as identified using the FSFI questionnaire. Limited clinical discussion, psychosocial stress, and socioeconomic constraints contribute to this issue. Integrating sexual health assessment and support into survivorship care is essential to improving overall patient well-being.Fungsi Seksual pada Pasien Kanker Serviks Berdasarkan Kuesioner Female Sexual Function Index di Rumah Sakit Umum Pusat Dr. Hasan Sadikin Bandung Tahun 2018 – 2023Abstrak Tujuan: Penelitian ini bertujuan untuk mengetahui gambaran fungsi seksual pasien kanker serviks yang menjalani terapi radiasi di RSHS menggunakan kuesioner Female Sexual Function Index (FSFI).Metode: Penelitian ini menggunakan metode potong lintang dan dilakukan pada pasien kanker serviks yang sedang menjalani terapi radiasi di RSHS antara Januari 2018 hingga Desember 2023. Data dikumpulkan menggunakan kuesioner FSFI dan dianalisis secara deskriptif.Hasil: Dari 100 pasien berusia 15 – 70 tahun, para pasien mengalami gejala yang saling tumpang tindih. Disfungsi seksual yang paling sering dilaporkan adalah vagina kering (90,63%), gangguan orgasme (79,17%), dispareunia (64,58%), dan penurunan libido (58%). Komorbiditas yang ditemukan meliputi hipertensi, diabetes melitus, dan infeksi saluran kemih.Kesimpulan: Sebagian besar pasien kanker serviks yang menjalani terapi radiasi mengalami disfungsi seksual, sebagaimana diidentifikasi melalui kuesioner FSFI. Kurangnya diskusi klinis, stres psikososial, dan keterbatasan sosial ekonomi turut berkontribusi terhadap masalah ini. Integrasi penilaian dan dukungan kesehatan seksual dalam perawatan pascaterapi sangat penting untuk meningkatkan kesejahteraan pasien secara menyeluruh.Kata kunci: fungsi seksual; kanker serviks; komplikasi radioterapi